Resistant starch: effect on rheology, quality, and staling rate of white wheat bread - Barros, Jefferson H. T. [UNESP]; Telis, Vânia R. N. [UNESP]; Taboga, Sebastião [UNESP]; Franco, Celia M. L. [UNESP] (Springer Nature, 2018)
The effect of the partial substitution (0, 10, 15, and 20%) of wheat flour with resistant starch (RS) on dough rheology and structure, and on the quality and staling rate of bread was evaluated. The results from farinograph, extensograph, alveograph, oscillatory rheological tests, and from confocal laser scanning microscopy, indicated that the substitution up to 15% of flour with RS slightly affected the dough structure, weakening it through dilution of gluten protein. Bread made with 15% of RS had specific volume, crumb moisture, and firmness values similar to those of the control bread (without RS), indicating very good quality. During storage, the RS breads had higher crumb moisture, lower firmness, and a lower retrogradation rate than the control bread. The lower retrogradation rate, in conjunction with the higher crumb moisture and high water-retention capacity of RS, was responsible for lower crumb firmness in bread containing up to 15% RS. Using wheat flour of high quality helped to minimize the deleterious effect of RS on the dough and provided high-fiber bread with high quality and low staling.
Keywords: Avrami equation; Bread quality; Firmness; Resistant starch; Rheology